EFEKTIVITAS PENGGUNAAN REBUSAN TUMBUKAN DAUN JAMBU BIJI UNTUK MENURUNKAN FREKUENSI DIARE PADA ANAK - Siti Aizah; Norma Risnasari; Nevi Listyawati (Jurnal EDUNursing, 2022)
Diarrhea is the occurrence of loose to liquid bowel movements (diarrhea) with a frequency of three or more times a day. The incidence of diarrhea can be accompanied by symptoms of dehydration, fever, nausea and vomiting, anorexia, weakness, paleness, sunken eyes, dry mucous membranes, and decreased urine output (Harris, et al (2017) cited in Lanida and Farapti, 2018). This type of research is descriptive analytic using a case study approach. The subject of this study was the patient’s mother who had used a decoction of crushed seed leaves to reduce the frequency of diarrhea in children. The results of the cross tabulation of the majority of data obtained were 24 respondents experienced a decrease in the frequency of diarrhea. Based on the results of the Spearman Rank Test Correlation Analysis, the sig. (2tailed) or probability (p) value is 0.000 with a significance level of 0.05 so that the p-value is 0.000 < 0.05, which means that the decoction of crushed guava leaves is effective in reducing the frequency of diarrhea so that Ho is rejected. The results showed that the effectiveness of the decoction of crushed guava leaves can reduce the frequency of diarrhea to 3 times a day. The decoction of the seed leaves containing tannins, flavonoids, essential oils, and alkaloids can be a solution to reduce the frequency of diarrhea, namely as a chelating agent with a spasmolytic effect that constricts the intestines so that peristalsis is reduced and also the spasmolytic effect can shrink bacterial cell walls or cell membranes, thereby disrupting cell permeability.  Keywords: Diarrhea, Decoction of crushed guava leaves, Decrease in the frequency of diarrhea in children.